A novel ultrasound approach in assessing IMAT in critically ill patients - Molinger, Jeroen; Whittle, John; Endeman, Henrik; MacLeod, David; Gupta, Rajan; Fudim, Marat; Haines, Krista L.; Barkauskas, Christina; Healy, Zachary; Wischmeyer, Paul; Bakker, Jan (Frontiers in Anesthesiology, 2024)
Background: Muscle wasting is a common finding in critically ill patients associated with increased days of mechanical ventilation in the ICU. Muscle wasting and associated morphological changes are hallmarks of ICU-acquired weakness. Muscle wasting can be diagnosed and quantified by muscle biopsy, but biopsies can cause multiple adverse effects. MuscleSound has developed a non-invasive, real-time novel MusculoSkeletal (MSK) ultrasound approach to measure the ratio between percentage intramuscular adipose tissue (%IMAT) with muscle cross-section area (MCSA) (termed IMAT-Index). The present study aimed to assess the IMAT-Index in ICU patients longitudinally and compare it to age-matched healthy controls. Methods: Transverse (short-axis) ultrasound images of the rectus femoris muscle were obtained upon admission and discharge in 35 ICU patients and compared to age-matched healthy controls (n=975). The echo intensity of the image taken from the muscle is used to automatically calculate the ratio between intramuscular adipose tissue by cm2 (IMAT-Index), the cross-sectional area of the muscle (MCSA), and muscle thickness (MT). Results: IMAT-Index was successfully measured in all subjects. The mean IMAT-index (%IMAT/cm2) upon admission was significantly higher in critically ill patients compared to healthy controls (7.4 ±4.3 vs 3.1±0.9, p<0.001). At ICU discharge, the IMAT-index increased in the ICU group compared to admission (8.1±3.5 vs 7.4±4.3, p<0.05). Conclusion: Real-time noninvasive MSK ultrasound IMAT-Index was higher in ICU patients than in healthy controls and increased during the ICU stay, both in male and female patients.